2007
DOI: 10.1303/aez.2007.651
|View full text |Cite
|
Sign up to set email alerts
|

Host characteristics related to host use by the flesh fly, Blaesoxipha japonensis (Diptera: Sarcophagidae), a parasitoid of adult grasshoppers

Abstract: We periodically collected adult grasshoppers of Parapodisma tanbaensis and P. subastris, in Kyoto, Japan, from 2001 to 2002, to determine which host characteristics were related to host use by the flesh fly, Blaesoxipha japonensis. The results indicated three host characteristics that were significantly related to the parasitism rate: host species, condition of the hind legs, and interaction between sex and body size. P. tanbaensis was parasitized more often than P. subastris because of its superior intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Miura and Ohsaki (2007) reported that host quality (expressed as the number of the last instar fly larvae emerging from a host) differed between sexes (more larvae emerged from female hosts than from male hosts) for a parasitoid fly ( Blaesoxipha japonensis (Hori)) that attacks Parapodisma spp. (grasshoppers).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miura and Ohsaki (2007) reported that host quality (expressed as the number of the last instar fly larvae emerging from a host) differed between sexes (more larvae emerged from female hosts than from male hosts) for a parasitoid fly ( Blaesoxipha japonensis (Hori)) that attacks Parapodisma spp. (grasshoppers).…”
Section: Discussionmentioning
confidence: 99%
“…However, because information on the existence of the sexual pheromones was lacking for the studied carabids, it is unclear whether female flies are unable to use host sexual volatiles, or whether these host beetles do not have sexual volatiles. Miura and Ohsaki (2007) reported that host quality (expressed as the number of the last instar fly larvae emerging from a host) differed between sexes (more larvae emerged from female hosts than from male hosts) for a parasitoid fly (Blaesoxipha japonensis (Hori)) that attacks Parapodisma spp. (grasshoppers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miura and Ohsaki (2015) suggested that the mortality caused by the emergence of the parasitoid fly Blaesoxipha japonensis (Diptera: Sarcophagidae) from adult P. subastris grasshoppers could be one of the costs of autotomy because P. subastris adults lacking a hind leg are more frequently killed by the emergence of this parasitoid fly than intact adults. In contrast to P. subastris, P. tanbaensis adults lacking a hind leg(s) and intact adults did not differ in the mortality caused by the emergence of B. japonensis (Miura and Ohsaki 2015), although the distribution of these two Parapodisma species is sympatric in the Kinki District (Miyatake and Kanoˆ1992;Miura 2003;Miura and Ohsaki 2007). However, it remains unknown what traits and/or factors may be re-lated to the frequency of hind leg loss in these Parapodisma adults in the wild.…”
Section: Introductionmentioning
confidence: 96%
“…Not only food plants and abiotic conditions, but also natural enemies, could differ among the microhabitats. As indicated by the difference in adult mortality caused by B. japonensis between P. subastris and P. tanbaensis (Miura and Ohsaki 2007), the fate of autotomized individuals could differ between these Parapodisma species (Miura and Ohsaki 2015).…”
Section: Introductionmentioning
confidence: 99%